Foreword - E Murer; P Niederer; B Radanov; A Rumo-Jungo; M Sturzenegger; F Walz (Pain Research and Management)
Widely known as whiplash, cervical acceleration/deceleration trauma typically occurs as a result of a rear end automobile collision. This might cause damage to vertebrae and cervical tissue in the neck, with no visible and easily attestable signs of injury. In recent years, whiplash has become a nightmare for doctors, lawyers, rehabilitation specialists, bioengineers and insurers, not only in Switzerland, but across the whole of western Europe, North America and Australia.